Role of extracapsular dissection in surgical management of benign parotid tumors - Iro, Heinrich; Zenk, Johannes (JAMA Otolaryngology - Head and Neck Surgery, 2014)
Hypothesis: Extracapsular dissection is a safe and effective surgical technique in the management of benign parotid neoplasms.
EVALuna2:19938